Evaluation of coriander (Coriandrum sativum L.) cultivars for yield and yield contributing characters in Gujarat - S Maiti, A K Phurailatpam, K A Geetha, R S Meena, (Journal of Spices and Aromatic Crops, 2016)
Nineteen cultivars of coriander (Coriandrum sativum L.) from diverse sources were evaluated in semi-arid conditions of Gujarat for observing the various morphological and yield characters. The highest plant height was found in Pant Haritama (97.27 cm) which was at par with RCr 435, ACr 209, JD 1, Co 4, RCr 20 and Sadhana. There were no significant differences in number of primary and secondary branches in all the cultivars. Highest seed yield plant-1 were observed in JD 1 (10.78 g) which was at par with Sudha, Sindhu and RCr 41.The lowest yield plant-1 were observed in RCr 20 (1.81gm). The minimum time taken for 50% flowering was observed in Sudha and RCr 41 (42.67 days) which were at par with that of Sindhu. The maximum time taken for 50% flowering was by RCr 20 (68.67 days). It was also observed that the time taken for days to full flowering in an umbel ranges between 8-14 days and the days to complete complete fruit formation in an umbel ranges from 14-20 days. It might be concluded from the study that the cultivars differed significantly in most of the parameters and offer a good scope of selection of cultivars for desired traits.